Comparison of diagnostic performance in on-site based CT-derived fractional flow reserve measurements. (August 2021) - Nozaki, Yui O.; Fujimoto, Shinichiro; Aoshima, Chihiro; Kamo, Yuki; Kawaguchi, Yuko O.; Takamura, Kazuhisa; Kudo, Ayako; Takahashi, Daigo; Hiki, Makoto; Kato, Yoshiteru; Okai, Iwao; Dohi, Tomotaka; et al.
Abstract: Background: Computed tomography fractional flow reserve (CT-FFR), which can be acquired on-site workstation using fluid structure interaction during the multiple optimal diastolic phase, has an incremental diagnostic value over conventional coronary computed tomography angiography (CCTA). However, the appropriate location for CT-FFR measurement remains to be clarified. Method: A total of 115 consecutive patients with 149 vessels who underwent CCTA showing 30–90% stenosis with invasive FFR within 90 days were retrospectively analyzed. CT-FFR values were measured at three points: 1 and 2 cm distal to the target lesion (CT-FFR1cm, 2cm ) and the vessel terminus (CT-FFRlowest ). The diagnostic accuracies of CT-FFR ≤ 0.80 for detecting hemodynamically significant stenosis, defined as invasive FFR ≤ 0.80, were compered. Result: Fifty-five vessels (36.9%) had invasive FFR ≤ 0.80. The accuracy and AUC for CT-FFR1cm and 2cm were comparable, while the AUC for CT-FFRlowest was significantly lower than CT-FFR1cm and 2cm . (lowest/1cm, 2 cm = 0.68 (95 %CI 0.63–0.73) vs 0.79 (0.72–0.86, p = 0.006), 0.80 (0.73–0.87, p = 0.002)) The sensitivity and negative predictive value of CT-FFRlowest were 100%. The reclassification rates from positive CT-FFRlowest to negative CT-FFR1cm and 2cm were 55.7% and 54.2%, respectively. Conclusion: The diagnostic performance of CT-FFR was comparable when measured at 1-to-2 cm distal to the target lesion, but significantly higher than CT-FFRlowest . The lesion-specific CT-FFR could reclassify false positive cases in patients with positive CT-FFRlowest, while all patients with negative CT-FFRlowest were diagnosed as negative by invasive FFR.